2017
DOI: 10.1016/j.rssm.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Increased educational attainment among U.S. mothers and their children’s academic expectations

Abstract: Existing research provides strong evidence that children with more educated parents have higher academic expectations for themselves, but has yet to consider how an increase in the education of lower educated mothers might alter the expectations of their children. In light of the historic increase in U.S. mothers’ pursuit of additional education, this study investigates this timely question using data from a nationally representative, intergenerational sample of U.S. children and mothers participating in the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…The results imply that the higher level of education attained by the mother is associated with a higher level of depressive symptoms for the son and a lower level of depressive symptoms for the daughter. A possible explanation for these dynamics is that higher education increases a mother’s expectations of her children [ 73 ]. Moreover, mothers have different expectations for their sons and daughters [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results imply that the higher level of education attained by the mother is associated with a higher level of depressive symptoms for the son and a lower level of depressive symptoms for the daughter. A possible explanation for these dynamics is that higher education increases a mother’s expectations of her children [ 73 ]. Moreover, mothers have different expectations for their sons and daughters [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional covariates/controls. We also included a dichotomous predictor for gender (DiPrete and Buchmann, 2013; Jacobs, 1996), a continuous measure of age at Wave 1 (Calcagno et al., 2007; Jacobs and King, 2002; Taniguchi and Kaufman, 2005), a categorical predictor of race/ethnicity (Desimone, 1999), a categorical measure of parental education level (capturing the highest attained by either parent) (Augustine, 2017; Dubow et al., 2009), a categorical measure of household income 7 (Desimone, 1999; Kim and Sherraden, 2011), and dummy variables capturing parental marital status (selected as a proxy, albeit imprecise, for single-parenthood) (Krein and Beller, 1988), sibling college going (whether or not students reported that they had a sibling in college at Wave 1) (Sewell et al., 1969; Sewell and Shah, 1968), parental financial assistance (Kim and Sherraden, 2011), and whether a student’s first institution was four year, or two year or less. Models 2B and 2D also include a dichotomous predictor of student expectations at Wave 1.…”
Section: Data Variables and Methodsmentioning
confidence: 99%
“…Family SES is also among the major determinants of students’ school achievement. 9 Among SES indicators, parental education is among the most stable aspects of family SES background, 15 which influence the quality of home learning settings 16 and higher levels of parental engagement in children’s schooling. 16 , 17 Children of low-educated parents more so than students with highly educated parents tend to demonstrate lower educational achievement.…”
Section: Introductionmentioning
confidence: 99%